2012
DOI: 10.4238/2012.march.14.5
|View full text |Cite
|
Sign up to set email alerts
|

Piperine inhibits cytokine production by human peripheral blood mononuclear cells

Abstract: ABSTRACT. Piperine, an amide isolated from Piper species (Piperaceae), has been reported to exhibit central nervous system depression, anti-pyretic and anti-inflammatory activity. Immunomodulatory and anti-tumor activity of piperine has been demonstrated in mouse carcinomas. However, there is little information available concerning the effect of piperine on humans. We evaluated the immunopharmacological activity of this compound in human immune cells. Human peripheral blood mononuclear cells (PBMCs) were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…For example, it has been shown that dietary curcumin in mice suppresses CD4 + T cell proliferation and IL-2 production [43] while in vitro curcumin supplementation inhibits T cell activation [44], human peripheral blood mononuclear cell proliferation and IL-2 production [40,42], and IL-2 synthesis as well as IL-2 signaling in mouse CD4+ T cells [41]. Although little information is available for piperine in this regard, some studies have indeed suggested that piperine may inhibit T cell-related functions [19,45]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that dietary curcumin in mice suppresses CD4 + T cell proliferation and IL-2 production [43] while in vitro curcumin supplementation inhibits T cell activation [44], human peripheral blood mononuclear cell proliferation and IL-2 production [40,42], and IL-2 synthesis as well as IL-2 signaling in mouse CD4+ T cells [41]. Although little information is available for piperine in this regard, some studies have indeed suggested that piperine may inhibit T cell-related functions [19,45]. …”
Section: Discussionmentioning
confidence: 99%
“…Silver nanoparticles strongly inhibited cytokine production, of INF-γ, IL-6, IL-8, IL-11, TNF-α and more weakly IL-5. The mechanism of anti inflammatory effect is due to cellular cytotoxicity a higher doses and also nano-silver was found to strongly effect the production of Th1cells that secrete the inflammatory cytokines IL-2, INF-γ which are involved in cellular immunity, and in chronic inflammatory disorders [17].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wang-Sheng et al [30] reported that piperine inhibits LPS-induced TNF-α, IL-6, IL-1β, and prostaglandin E2 (PGE-2) production in BV2 microglial cells. In the human peripheral blood mononuclear cells (PBMCs), piperine was found to inhibit IL-2 and interferon gamma (IFN-È) [31]. Piperine inhibits the production of PGE2 and NO induced by LPS while decreasing TNF-α, inducible NO synthase (iNOS) and cyclooxigenase-2 (COX-2) in RAW264.7 cells, resulting in anti-inflammatory activity [32].…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%